Дослідження параметрів процесу ферментації хумусу стартовими культурами - Гніцевич, Вікторія Альбертівна; Доронін, Кирило Анатолійович; Gnitsevych, Victoriya; Doronin, Kyrylo (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті наведено результати дослідження параметрів процесу ферментації хумусу із застосуванням стартових культур молочнокислих бактерій. Обґрунтовано доцільність використання керованої ферментації для покращення фізико-хімічних та сенсорних властивостей продукту. Досліджено вплив дози стартової культури, температури та тривалості ферментації на динаміку кислотності та накопичення ароматичних сполук у хумусі. Встановлено закономірності зміни pH та інтенсивності утворення діацетилу в умовах холодної ферментації. Показано, що ферментація за температури 2…6 °C забезпечує стабільний перебіг мікробіологічного процесу без різкого підвищення кислотності. Визначено раціональні параметри ферментації, які дозволяють керовано формувати смак і аромат хумусу та підвищувати його споживчу привабливість. /// EN: The article presents the results of a comprehensive study of the controlled fermentation process of hummus using lactic acid bacteria starter cultures aimed at substantiating rational technological parameters and ensuring stable quality characteristics of the final product. The relevance of the study is driven by the growing global demand for fermented plant-based foods with functional and vegan orientation, as well as by the insufficient scientific knowledge regarding fermentation processes of paste-like legume-based products, particularly hummus. Traditional hummus production technology does not involve controlled fermentation, which limits the possibilities for regulating its physicochemical, microbiological, and sensory properties. The aim of the study was to scientifically substantiate and experimentally determine rational parameters of the hummus fermentation process using Lactobacillus rhamnosus and Lactococcus lactis starter cultures under lowtemperature (cold fermentation) conditions. The effects of starter culture dosage, fermentation temperature, and process duration on pH dynamics and the accumulation of flavor-active compounds, particularly diacetyl, were investigated as key indicators of fermentation efficiency and consumer acceptability. Experimental studies were conducted using starter culture dosages in the range of 1 ⋅ 106 to 1 ⋅ 108 CFU/g, fermentation temperatures of 2…6 °C, and a process duration of up to 30 days. The results demonstrated that hummus fermentation is characterized by a slow decrease in pH values, which is attributed to the biochemical characteristics of chickpea-based raw materials, the limited content of readily fermentable carbohydrates, and the high buffering capacity of the product. It was established that variation in starter culture dosage does not cause significant differences in final pH values; however, it affects the intensity of the initial fermentation stage. A starter culture concentration of 1 ⋅ 107…1 ⋅ 108 CFU/g was identified as optimal. The study confirmed that fermentation temperature significantly influences diacetyl accumulation. The most intensive diacetyl formation was observed at 6 °C, which is associated with higher metabolic activity of lactic acid bacteria under reduced cold stress compared to lower temperatures. It was found that the main accumulation of diacetyl occurs during the first 7 days of fermentation, after which its concentration stabilizes due to substrate depletion and the transition of microorganisms to the stationary growth phase. The obtained results confirm the feasibility of using starter cultures for the controlled formation of the flavor and aroma profile of hummus and provide a scientific basis for the implementation of fermented hummus technology in the production of functional and craft food products.
Study of the parameters of the humus fermentation process with starter cultures
Keywords: молочнокисле бродіння; бобові культури; холодна ферментація; кислотність; діацетил; ароматичний профіль; функціональні продукти; пастоподібні системи; lactic acid fermentation; legumes; cold fermentation; acidity; diacetyl; aroma profile; functional product; paste-like systems